Pattern Versus Change: Community-Based Dyadic Heart Failure Self-Care. (February 2018) - Buck, Harleah G.; Hupcey, Judith; Watach, Alexa
It is imperative that dyadic heart failure (HF) self-care be carefully examined so we can develop interventions which improve patient outcomes. The purpose of this study was to qualitatively examine how patient/informal caregiver dyads mutually engage in managing the patient's HF at home. Twenty-seven dyads were interviewed using a theoretically derived interview guide. All interviews were digitally recorded and professionally transcribed, and iterative thematic analysis was conducted. Three descriptive themes emerged—Mutual engagement in self-care involves maintaining established patterns of engagement across the life course of the relationship, changing patterns according to whether it is day-to-day care or symptom management, and mobilizing the help of a third party as consultant. These themes reveal the dyadic conundrum—whether to change or remain the same in the face of a dynamic and progressive condition like HF. The themes suggest potential targets for intervention—interventions focused on the relationship or caregiver activation.